Evaluasi Kinerja Pemerintah Kabupaten Pemalang, 2005-2007 - Isiqomah Isiqomah; Ratno Purnomo (EKO-REGIONAL, 2010)
Monitoring and evaluation (monev) are important to analyze the achievement goal through many activities so corrective policies shoud be done immediately. This research evaluates the government performance of Pemalang regency using 117  indicators based on PP No.6/2008. Some data SKPD are displayed from 2005 until 2007. However, data used to compare indicator among regencies are only displayed in 2006. This research recommend which indicators are good and which ones are necessary to accelerate.         Keyworlds: monitoring, evaluation, otonomy